Comparison of the effects of unidirectional and sign‐alternating temperature gradients on the sintering of ice spheres. Issue 4 (4th December 2016) - Wang, Xuan; Baker, Ian
Abstract: To simplify the complex snow structures that occur in nature, polycrystalline ice spheres were produced and arranged vertically to model the sintering process. By controlling the temperatures on both the top and bottom of the ice sphere array, the effect of upward and downward vapor transfers was examined. The evolution of the neck areas between ice spheres was observed using X‐ray computed microtomography. As frequently observed under the basal part of a snow layer and previous experiments of snow temperature gradient metamorphism, depth hoar structures were formed along neck areas and their formation was found to be directly related to the vapor transfer direction. To model the temperature gradient inversion that can be induced in nature by daily cycles of radiative heating and cooling, we also performed sign‐alternating temperature gradient experiments on the ice sphere arrays. The morphological evolution of the neck and the associated vapor transfer were examined through image analysis and 2D modeling. The final microstructures of the neck area turned out to be a symmetrical distribution of ice protrusions bridging neighboring ice spheres.